العبارات الرابطة ودلالتها الاستدراكية في النص العربي: Linking Verbs and Their Remedial Significance in The Arabic Text - Hisyamuddin Bin Mohd Yusof; Nurul Fatihah Hanafi (RABBANICA - Journal of Revealed Knowledge, 2022)
فعل الربط دوره المهم في اتساق النص واعتبر من أهم أساسيات التكوين في النص ثم جرى معناه على الطريقين النحوي والمعجمي وكلاهما يلونان القضية في النص ببنية الكلمة والجملة. فالدراسة المستفيضة عن آليات الربط ضرورية للغاية، ثم أتت ملامح الدلالة في تأصيل ما دلت تلك الآليات نفسها وما دلت إذا كان في النص، وتطورت الدلالة السياقية في توضيح معنى النص على وجه الدقة والرقة. فتناولت هذه الدراسة دلالة العبارات الرابطة الاستدراكية في النص العربي لأهميتها في الربط بين أفكار النص. دلالة الاستدراك هي احدى الدلالات التي تحمل عليها العبارات الرابطة في نحو النص فهناك عدد كبير من العبارات الرابطة المستعملة في النص العربي التي تقل البحث عنها في الدراسة اللغوية الحديثة، فالدراسة عنها تعد أمرا مهما للغاية. تطرقت الدراسة على منهج التحليل، ستقتصر الدراسة على مفهوم الاستدراكية في ربط النص فضلا عن دلالتها بين أفكار النص، وهدفت إلى بيان أهمية دلالتها الاستدراكية في النص العربي وتأثيرها هذا التجديد في تحقيق معاني النص بشكل أدق، وتوصلت إلى عدة نتائج أهمها أن هناك تطورا في تدليل قصد النص العربي خلال وظيفة العبارات الرابطة في توصيف طبيعة النص. Linking verbs is very important for text cohesion and is recognized as one of the most essential elements in building the text. Its meaning was carried out on the grammatical and lexical paths which also pattern statements in text with word and sentence structure. Extensive study of the linking mechanisms is necessary, then the features of the sign came in rooting what those mechanisms themselves indicated and what they indicated if it was in the text, and the contextual significance developed in clarifying the meaning of the text precisely and tenderly. This study dealt with the significance of the remedial linking phrases in the Arabic text due to their importance in linking the ideas of the text. The connotation of catch-up is one of the indications that the connecting phrases carry in the syntax of the text. There are many connecting phrases used in the Arabic text that are less searched for in modern linguistic studies, so studying them is very important. The study dealt with the method of analysis. The study will be limited to the concept of remedial in linking the text as well as its significance between the ideas of the text. The intent of the Arabic text is through the function of connecting phrases in describing the nature of the text.